2011
DOI: 10.1136/adc.2010.204636
|View full text |Cite
|
Sign up to set email alerts
|

Once daily insulin detemir in cystic fibrosis with insulin deficiency

Abstract: The aim of this study was to determine if once daily insulin detemir reverses decline in weight and lung function in patients with cystic fibrosis (CF). 12 patients with early insulin deficiency and six with CF related diabetes (aged 7.2-18.1 years) were treated for a median of 0.8 years. Changes in weight and lung function following treatment were compared to pretreatment changes. Before treatment, the change in weight SD score (ΔWtSDS), percentage of predicted forced expiratory volume in 1 s (Δ%FEV(1)) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 7 publications
3
64
0
1
Order By: Relevance
“…However, in the study by Minicucci et al16 there was a 10% decrease in FEV1 in the year prior to the intervention, which may be a bias because even CFRD patients have no such decline in this parameter. Koloušková et al17 and Drummond et al12 , who had a more consistent number of cases, found that FEV1 was lower in the untreated group compared to those treated with insulin, which confirms the results described by Dobson et al6 Bizarri et al20 , and Hameed et al19 …”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…However, in the study by Minicucci et al16 there was a 10% decrease in FEV1 in the year prior to the intervention, which may be a bias because even CFRD patients have no such decline in this parameter. Koloušková et al17 and Drummond et al12 , who had a more consistent number of cases, found that FEV1 was lower in the untreated group compared to those treated with insulin, which confirms the results described by Dobson et al6 Bizarri et al20 , and Hameed et al19 …”
Section: Discussionsupporting
confidence: 57%
“…Bizzarri et al,20 Mozzillo et al,18 and Hameed et al19 found a significant increase in FEV1 after the use of insulin. Koloušková et al17 found that, at the end of follow-up, intervention group had higher FEV1 compared to control group.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This before-and-after study 161 looked at the effect of a single daily dose of insulin detemir on weight change and lung function in six patients with CFRD and 12 with 'early insulin deficiency' , defined by peak BG level during OGTT but with a 2-hour level of < 11.1 mmol/l. The median age of the patients was 12.5 years, and all but one had exocrine pancreatic insufficiency.…”
Section: Hameed 2011mentioning
confidence: 99%